Nurses and their work in tuberculosis control in the Western Cape : too close for comfort - Van der Walt, Hester Maria (Department of Public Health and Family Medicine, 2017)
The setting for the research is the urban areas of Cape Town, South Africa where the notification rate of tuberculosis is the highest in the world. Despite the availability of modern drugs, the cure rate is low and approximately 40% of diagnosed patients do not adhere to treatment. This has serious implications for the spread of multiple drug-resistant tuberculosis. The relationship between the patient and health care providers is one of the main determinants of compliance to medical treatment. The main aim of the thesis is to develop an understanding of how nurses experience their work with patients who have pulmonary tuberculosis. The research explores how nurses interact with patients, how nurses perceive their relationship with patients and the processes and organisational arrangements which contribute to the patterns of nurse-patient interaction. The interpretive research design was largely informed by an ethnographic approach. The iterative research process led to several sub-studies; the analysis of each sub-study led to a further cycle of data collection. Data collection techniques include participant observation of nurse-patient interaction and depth interviews with nurses and key informants. An exploration of opportunities to change the prevailing work patterns yielded data on nurses' responses to change. The data were captured as field notes or audio taped and analysed thematically by using qualitative methods and by the application of psychodynamic theory. The research identifies task orientation and patient-centredness as the main patterns of nurse-patient interaction. Task orientation was found to be the dominant work pattern. Its origins are traced to the colonial history and to the influence of Taylorist labour practices. Task orientated work patterns are maintained because of complex mechanisms which operate at both intrapersonal and interpersonal levels. It is argued that the history of racial politics and racial identity has influenced the ways in which nurses manage the degree of distance between themselves and patients. The findings suggest that the closer the nurses identify with patients in terms of ethnic background, the more the nurses may feel the need to distance themselves from the patients. The notion of tuberculosis as a stigmatised disease, the concept of compliance, and the implementation of control measures such as directly observed therapy are critically examined. An exploration of the illness experiences of nurses who become infected with tuberculosis, provides an opportunity to explore how nurses perceive the role of the caregiver when they are in the unfamiliar position of being patients. The findings have implications for public health interventions aimed at transforming nurse-patient interaction. It is recommended that change management processes explicitly acknowledge the consequences of decades of apartheid policies and practices on the behaviour of health professionals and the users of health services. In the years to come change agents will need to address the emotional pain of the past, as well as the more well-known sources of organisational resistance to change.